Modeling the impact of early exhaust valve opening on exhaust aftertreatment thermal management and efficiency for compression ignition engines. (September 2015) - Roberts, Leighton; Magee, Mark; Shaver, Gregory; Garg, Akash; McCarthy, James; Koeberlein, Edward; Holloway, Eric; Shute, Raymond; Koeberlein, David; Nielsen, Douglas
In response to strict emissions regulations, engine manufacturers have implemented aftertreatment technologies to reduce the tailpipe emissions from diesel engines. The effectiveness of most of these systems is limited when exhaust temperatures are below 250°C. This is problematic during cold start and at low-load engine operation when the exhaust gas temperature is too low to keep the aftertreatment working effectively. The implementation of variable valve actuation strategies, including early exhaust valve opening, has been proposed as a means to elevate exhaust temperatures. Early exhaust valve opening results in hotter exhaust gas; however, more fueling is needed to maintain brake power output. This article outlines an analysis of the impact of early exhaust valve opening on exhaust temperature (measured at the turbine outlet) and the required fueling. An experimentally validated model is developed, which relates fueling increase with the timing of exhaust valve opening. This model is used to generate expressions for brake thermal efficiency and turbine out temperature as a function of exhaust valve opening. These expressions are used to evaluate the impact of early exhaust valve opening over the entire low-load operating space of a diesel engine. The model predicts an approximate 30 °C–100 °C increase in turbine out temperature at a given commanded exhaust valve opening of 90° before nominal, which is sufficient to raise many low-load operating conditions to exhaust temperatures above 250 °C; however, the analysis also predicts penalties in brake thermal efficiency as large as 0.05 points.